Academic skills and beyond: A resource based approach to support student success in higher education - Hitch, Danielle; Goldingay, Sophie; Hosken, Norah; Lamaro, Greer; Macfarlane, Susie; Nihill, Claire; Ryan, Juliana; Farrugia, Dennis (Journal of Academic Language and Learning, 2012)
An increasingly diverse range of students are entering higher education, bringing with them a vast range of experiences, skills and pre-existing knowledge. However, approaches to increasing student participation (and therefore success) to date have focused on strategies aimed at supporting non-traditional students to “fit in”, rather than changing existing structures to accommodate their needs. This paper will outline a resource-based approach to student success, which capitalises on the resources and capacities existing within the student, within their performance of the student role and within the environment that surrounds their learning. This paper will report on a study and propose a resource based approach to student success. Three main sites or domains are identified as a focus of this approach – intrapersonal resources, skills resources and environmental resources. These domains interact with each other to support student success, and three potential methods for implementing a resource based approach are highlighted in the spaces where they intersect. Pedagogical design, mapping and matching, and learning support all have a role in enabling both students and universities to make the most of their existing resources and develop new ones.